MANAGEMENT OF OVERRIDING FEMUR FRACTURE IN A CAT: A CASE REPORT - Das, B C; Prasad, A Arun; Kumar, R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Long bone fractures are common and account for 50% of all feline fractures (Scott and McLaughlin, 2007) and the femur is one of the most commonly fractured bones in dogs and cats (Maala and Celo, 1975 and Johnson et al., 1989). Harasen (2003) reported that 45% of long bone fractures were femoral fractures and 28% of long bone fractures occurred in the femoral diaphysis. The femur fractures in cat are readily diagnosed by palpation and radiography. In almost all cases, surgical intervention is indicated to reduce the fracture properly and provide stability. A number of fixation methods are available for long bone fracture repair, each of which has advantages and disadvantages. Intramedullary pinning is a popular method of long bone fracture repair in cat because of pin insertion is technically relatively easy and the equipment and implants are cheap and readily available (Scott, 2005). In cats, virtually all types of fracture, even severely comminuted fractures of the diaphysis can be successfully treated by the use of intramedullary fixation used in conjunction with cerclage wires (Denny and Butterworth, 2000 ). The present case describes the outcome of femur fracture management in a cat.
Keywords: MANAGEMENT; OVERRIDING FEMUR; CASE REPORT